(X-2)/6=(x+10)/8

Simple and best practice solution for (X-2)/6=(x+10)/8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-2)/6=(x+10)/8 equation:


x in (-oo:+oo)

(X-2)/6 = (x+10)/8 // - (x+10)/8

(X-2)/6-((x+10)/8) = 0

(X-2)/6+(-1*(x+10))/8 = 0

(8*(X-2))/(6*8)+(-1*6*(x+10))/(6*8) = 0

8*(X-2)-1*6*(x+10) = 0

8*X-6*x-76 = 0

(8*X-6*x-76)/(6*8) = 0

(8*X-6*x-76)/(6*8) = 0 // * 6*8

8*X-6*x-76 = 0

8*X-6*x-76 = 0 // - 8*X-76

-6*x = -(8*X-76) // : -6

x = (-(8*X-76))/(-6)

x = (76-(8*X))/(-6)

x = (76-(8*X))/(-6)

See similar equations:

| -7-3x=8 | | 23/10=6-m | | x=2x+200 | | 6-m=23/10 | | 0.35/100x100 | | 21-4n=5 | | 8Y+3=6Y-13 | | -m^2-8m=16 | | -3m^2+27m=0 | | -24+6x=30 | | 5x+22-3x=45 | | 15-x/2=x/3 | | 5x+22-3x= | | 12b^2+25b+1=0 | | 12x=-3(-5+x) | | 2x^2+12x+24/2=0 | | 2(2x+3)=3(x+2)+x | | P=7L+7W | | 2x^2+12x+24=0/2 | | -(m-1)=13-4m | | 3/8=-1/2p | | 10k-4k+2k-6k=20 | | 14.2z+11.9-9.6z-15.2= | | 10k-4k+6k=20 | | 550x=1680x | | -(12-5f)=3 | | 1.9-x=x+0.1 | | 5x+2y-3=0 | | 6n-3n+2n=20 | | -30+5y=15 | | 5c+2=2c+17 | | 6(x+2)=2(2x-4) |

Equations solver categories